Lexical Ambiguity in the Lyrics of the Cigarettes After Sex Album: A Semantic Study - Chin, Francis Varian; Gunawan, Hero (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2024)
This study aims to analyze lexical ambiguity in the song lyrics by Cigarettes After Sex. The main focus of this study is to identify the types of words that having lexical ambiguity and explore the meanings of the words contained in these words in the context of the album with a semantic approach. This study uses a qualitative descriptive method to examine the lexical ambiguity of the lyrics in depth. The results show that the lyrics frequently use lexical ambiguity with multiple meanings, including nouns, adjectives, and verbs. This ambiguity not only enriches the meaning of the lyrics by adding the meaning of the lyrics but also creates a subjective and personal listening experience for the listener. Ambiguous words are often used to describe feelings of love, longing, sadness, and emotional complexity in human relationships. This study concludes that lexical ambiguity plays an important role in creating emotional depth and allowing listeners to find diverse meanings according to their own experiences and emotional contexts. This ambiguity also increases the complexity of the lyrics, making it an effective poetic tool in conveying nuances of emotion and multi-layered meanings.